Kontribusi Masyarakat terhadap Penegakan Hukum Lingkungan Berdasarkan UU No. 32 Tahun 2009 - Ellisha Putri; Handan Salsa; Ika Putri; Izaldi Pramudia; Reza Fediansya; Revania Meita; Sheyla Dwi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The 1945 Constitution of the Republic of Indonesia states that every Indonesian citizen has the right to a clean and healthy living environment. Unsustainable development and exploitation of natural resources have led to a drastic decline in the quality of the living environment in Indonesia. This has resulted in environmental damage, such as pollution and loss of biodiversity. One important instrument in the effort to protect the environment is environmental law, which is regulated by Law Number 32 of 2009 concerning the Protection and Management of the Living Environment (Environmental Protection Law). Although the Environmental Protection Law provides a comprehensive legal framework, law enforcement in the field still faces several issues, such as limited resources and low legal awareness. In such situations, community participation can be strategically utilized to enhance the efficiency of environmental monitoring and law enforcement. The aim of this research is to descriptively examine the function of community participation in environmental law enforcement as regulated by the Environmental Protection Law, as well as to analyze how effective and challenging its implementation is.